ANALYSIS OF EMPLOYEES TURNOVER INTENTION AT HIKMAH FOOD PT HIKMAH SEJAHTERA - Dwiky Nugraha, Ferdiansyah; Santoso, Bowo (PT Larva Wijaya Penerbit, 2025)
The objective of this research is to investigate and evaluate how employee turnover intention PT Hikmah Sejahtera is impacted by job motivation and compensation. A quantitative method was used, applying a census sampling technique to a population of 50 employees permanent and contract staff. The data was gathered by a questionnaire, and the Partial Least Square (PLS) method was used for analysis. Analysis's findings demonstrate that employee turnover intention is significantly impacted negatively by remuneration. Conversely, work motivation showed a negative, but not significant, influence. The implication is that compensation serves as a stronger predictor, where a substantial increase in compensation is capable of mitigating turnover intention. Meanwhile, although work motivation is an important variable, an increase in compensation is more effective in reducing employees' desire to leave the organization. Therefore, the company is recommended to revitalize elements of work motivation and ensure a fair and competitive compensation system to minimize turnover intention.